Pengaruh Literasi Keuangan, Kompetensi Sumber Daya Manusia, dan Digitalisasi Marketing Terhadap Kinerja UMKM Bidang Kuliner di Kabupaten Banyumas - Ambarwanti, Ambarwanti; Farida, Yusriyati Nur (Jurnal Riset Akuntansi Soedirman, 2025)
This study is a quantitative research using primary data. This study aims to find out and analyze the influence of financial literacy, human resource competence, and marketing digitalization on the performance of MSMEs in the culinary sector in Banyumas Regency. The research data collection technique uses the offline and online questionnaire distribution method. The research population is MSMEs in the culinary sector in Banyumas Regency which is found on the SSCPurwokerto Instagram account. The sample in this study was 81 MSME respondents in the culinary field with a sampling technique, namely simple random sampling. The data analysis in this study uses the Statistical Package for the Social Sciences (SPSS). The results of this study show that: (1) Financial literacy has a positive effect on the performance of MSMEs, (2) Human resource competence has a positive effect on the performance of MSMEs, (3) Digitalization marketing has a positive effect on the performance of MSMEs. The implication of this study is that it is expected that the government will take part in improving the performance of MSMEs which is influenced by several factors. MSME actors also improve even more about what factors can affect the performance of the MSMEs themselves so that the business they run can develop and be much better in the long term.